Effect of traditional processing of hausa koko (millet porridge) and ekoegbeme (cooked dehulled maize grits) on aflatoxins. - Ankomah, Albert (KNUST, 2026)
A thesis submitted to the Department of Food Science and Technology, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirements for the award of MASTER OF SCIENCE IN FOOD QUALITY MANAGEMENT